Epigenetic role of thymoquinone: impact on cellular mechanism and cancer therapeutics. Issue 12 (December 2019) - Khan, Md. Asaduzzaman; Tania, Mousumi; Fu, Junjiang
Highlights: Thymoquinone is a natural product with anticancer activity. Thymoquinone can methylate or demethylate DNA. Thymoquinone can interfere with the histone acetylation/deacetylation process. Thymoquinone can regulate miRNA expression. Abstract : Thymoquinone is a natural product known for its anticancer activity. Preclinical studies indicated numerous mechanisms of action by which thymoquinone exerts its effects on cancer cells. Recent evidence has indicated that thymoquinone can modulate epigenetic machinery, like modifying histone acetylation and deacetylation, DNA methylation and demethylation, which are among the major epigenetic changes that can contribute to carcinogenesis. Moreover, thymoquinone can alter the genetic expression of various noncoding RNAs, such as miRNA and lncRNA, which are the key parts of cellular epigenetics. This review focuses on cellular epigenetic systems, epigenetic changes responsible for cancer and the counteraction of thymoquinone to target epigenetic challenges, which might be among the mechanisms of the thymoquinone effect in cancer cells.